Psicopatología del yo y su problema de adaptación por consumo de marihuana - Pereira Cevallos, Germania Valeria (2018)
In short, as human beings we must know each of the alterations that the individual goes through and one of the most common is the psychopathology of the ego and problems of adaptation. That is why in the case study we will know, analyze and evaluate Javier a 16-year-old adolescent consumer of marijuana which presents alterations and makes it difficult to evaluate and understand reality or in turn overcome the external and internal threats that the individual undergoes throughout his life in order to see what would be the stressors that affect the individual and produce this type of alterations. Having as priority each of the alterations of the individual we must know what are the stressors of the environment and difficulties of adaptation that are the main drivers of the research having scientific basis that show that the regions that control the impulses are not fully formed at these ages , which is a valid reason why it is necessary to deepen and know the risks that this adolescent presents and the levels of vulnerability that is an important part since it is in these ages where young people are more accessible to risks, whether these are drug problems , gangs or family rebellion. The case study was carried out by means of a series of tests carried out by psychotherapeutic techniques, this being the taking of clinical histories, psychometric tests and semi-structured interviews with the patient and mother of the same to have a better vision about the problem.